Work in Progress: Extending Virtual Prototypes of Microprocessor Architectures with Accuracy Tracing - Kliemt, Johannes; Fey, Dietmar (Proceedings of the 13th International Conference on Simulation and Modeling Methodologies, Technologies and Applications - SIMULTECH, 2023)
Virtual Prototypes of microprocessor architectures (VPs) extensively support the software development process with the ability to build virtual Hardware in the Loop (vHIL) test benches. A physical hardware is not necessary since the VP is also a functional simulation model, although with reduced accuracy. The actual deviation to the physical hardware in the time domain is mostly unspecified and dependent on the executed application software. This leads to issues when used in the development of software with real time requirements. The authors propose a new way of determining this inaccuracy via a trace unit integrated into the VP. Accuracy is now determined for each application software on the fly taking its individual paths through the model and not by a unrelated general set of accuracy benchmarks. A more reliable statement on the later temporal behavior on the physical hardware can therefore be given.<br
Keywords: vHIL; Virtual Prototypes